SKRINING KETAHANAN BEBERAPA JENIS TANAMAN CABAI RAWIT TERHADAP CEKAMAN KEKERINGAN - APRIZAL, MUHAMMAD; BOER, DIRVAMENA; HADINI, HAMIRUL; SADIMANTARA, I GUSTI RAY; MUHIDIN, MUHIDIN; ANIMA HISEIN, WAODE SITI (Jurnal Agroteknos, 2023)
The aim of this research is to obtain information on the resistance of several local cayenne pepper varieties from Southeast Sulawesi to drought stress. The study was conducted at Field Laboratory II, Faculty of Agriculture, Halu Oleo University, Kendari, which took place from January to June 2022. The research consisted of two experiments, namely the seed phase and the plant phase. The first experiment used a Factorial Randomized Block Design (RAK). The first factor was drought stress, consisting of 3 levels of PEG concentration (0, 7.5, and 15%). The second factor was the type of cayenne pepper, including 2 national varieties: Dewata and Bara, as well as 4 local cultivars from Konsel, Konawe, Muna, and Kendari. The second experiment also used a Factorial Randomized Block Design (RAK). The first factor was watering with field capacity (KL): 100, 50, and 25%. The second factor was the same as in the first experiment, which was the type of cayenne pepper. The first experimental variables were germination ability, germination weight, and drought stress index in the seed phase. The second experimental variables were plant height, number of leaves, root length, fruit weight, and stress tolerance index in the plant phase. Observational data were analyzed using variance analysis, followed by the BNJ test with a 95% confidence level. The results of the research showed that there was an interaction between the drought stress treatment and the type of cayenne pepper plant, which had a significant effect on plant height, root length, and fruit weight per plant. However, for germination ability, germination weight, and the number of leaves, each factor had an independent effect. With the 15% PEG treatment in the germination phase, the resistant cayenne pepper varieties were the cultivars from Muna and Konsel, while the 25% field capacity treatment for the plant phase of resistant cayenne pepper were Dewata and Bara varieties, cultivars from Muna and Konsel.